2017
DOI: 10.1002/adfm.201704864
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Activation of Charge Transfer in Anionic Redox Process for Li‐Ion Batteries

Abstract: Anionic redox processes are vital to realize high capacity in lithium-rich electrodes of lithium-ion batteries. However, the activation mechanism of these processes remains ambiguous, hampering further implementation in new electrode design. This study demonstrates that the electrochemical activity of inert cubic-Li 2 TiO 3 is triggered by Fe 3+ substitution, to afford considerable oxygen redox activity. Coupled with first principles calculations, it is found that electron holes tend to be selectively generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 44 publications
(41 reference statements)
3
52
0
Order By: Relevance
“…After charging to the 4.5 V voltage plateau, a reverse shift is observed for the Co K‐edge (Figure S10a, Supporting Information), indicating a possible modification of the Co local structure that induces strong electronic redistributions along the CoO bonds. This is similar to the reductive coupling mechanism of Ru in Li 2 RuO 3 , which can enhance the stability of Li‐rich cathode materials . (More details of charge compensation mechanism in the first cycle can be seen in the Supporting Information.…”
supporting
confidence: 60%
“…After charging to the 4.5 V voltage plateau, a reverse shift is observed for the Co K‐edge (Figure S10a, Supporting Information), indicating a possible modification of the Co local structure that induces strong electronic redistributions along the CoO bonds. This is similar to the reductive coupling mechanism of Ru in Li 2 RuO 3 , which can enhance the stability of Li‐rich cathode materials . (More details of charge compensation mechanism in the first cycle can be seen in the Supporting Information.…”
supporting
confidence: 60%
“…Different from the conventional Lirich oxide cathode materials, the Li-Mo cation mixing occurs in the Li layer and is finished in one charge/discharge cycle in this material. [13,14] It delivers a reversible capacity of 250 mAh g −1 due to the triggering effect of the Fe atoms, via which the neighboring oxygen can participate in the charge compensation. [9] Recently, Li-rich materials with the Li-TM mixing rocksalt-type structure, such as Li 1.3 Nb 0.3 Mn 0.4 O 2 (0.43Li 3 NbO 4 ·0.57LiMnO 2 ) [10] and Li 1.2 Ti 0.4 Mn 0.4 O 2 (0.5Li 2 TiO 3 ·0.5LiMnO 2 ), [11] were proposed as high-capacity electrode materials, in which the formation of percolating network [12] for the Li-excess system opens up an avenue for the Li diffusion in the Li-TM mixing rocksalttype structure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Li 2 TiO 3 -LiFeO 2 with a Li-TM mixing Li-layer (a hybrid structure of 13% C2/c and 87% Fm m 3 ) was synthesized in different laboratories. [13,14] It delivers a reversible capacity of 250 mAh g −1 due to the triggering effect of the Fe atoms, via which the neighboring oxygen can participate in the charge compensation. In addition, we found that doping of Ti 4+ ions (2.5%) in the Li-layer of LMR can significantly improve its structural and performance stability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been enormous interest for lithium ion batteries (LIBs) due to their significant merits such as small volume, long cycle life, high specific capacity, and good safety [1][2][3], which are applicable in various fields such as digital products, satellites, and portable mobile tools [4][5][6][7]. Compared to the traditional anode material (graphite has a low specific capacity of 372 mAh g −1 ) [8][9][10], transition metal oxides (TMOs) can deliver a higher theoretical specific capacity (500-1000 mAh g −1 ) that is promising to replace the conventional graphite material in LIBs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of metal oxides nanoparticles on graphene-based materials could enhance the electrical conductivity and buffer volume variation of the electrode and could further improve the electrochemical performance of LIBs [31]. For instance, Yang et al [32] presented a facile strategy for the synthesis of graphene-coated Co 3…”
Section: Introductionmentioning
confidence: 99%